(untitled) (Journal of Asian Geography, 2024)
Bangladesh is among the countries most vulnerable to climate change. This vulnerability stems not only from its exposure to climate change and intensified extreme weather events but also from the way adaptation policies and projects have been designed using a technocratic, top-down approach. As a result, much of the adaptation has led to negative consequences for certain groups—often the most vulnerable—who depend directly on nature for their livelihoods. This outcome, known as maladaptation, has been particularly pronounced. This paper conducts a systematic review of peer-reviewed literature since 2014, the year when maladaptation first gained significant attention in the IPCC’s fifth report. The goal is to assess the current state of research on climate change adaptation in Southwestern coastal Bangladesh, particularly around the Sundarbans, the largest contiguous mangrove forest in the world. The review aims to identify research gaps and discuss key lessons learned. Keywords used in the review include 'maladaptation', 'barriers to adaptation', 'ecosystem-based adaptation', and 'gender', as these concepts are all interrelated to some degree. The review highlights significant research gaps across all topics, as well as a geographical imbalance in the distribution of studies within the region. Given the prevalence of maladaptation in Bangladesh, it is crucial that more research focuses on this issue to gather insights and reduce the risk of maladaptation in future climate change adaptation projects in the country.